Research on milk homogenization in the stream homogenizer with separate cream feeding - Samoichuk, Kyrylo; Zhuravel, Dmytro; Viunyk, Olga; Milko, Dmytro; Bondar, Andrii; Sukhenko, Yuriy; Sukhenko, Vladyslav; Adamchuk, Leonora; Sergey, Denisenko (Potravinarstvo, 2020)
Homogenization, which is used in the technological schemes of production of most dairy products, is the most energy-intensive of the processes of mechanical processing of milk. One promising way to increase the energy efficiency of homogenization is to use separate homogenization and to use a little-researched stream homogenizer with separate cream feeding. The principle of its action is to pre-divide milk into cream and skim milk, and feed the fat phase with a thin stream into the stream of skim milk. This creates the conditions for achieving the high value of the Weber criterion - the main factor in the dispersion of milk fat. The purpose of these researches is to conduct experimental studies and determine the energy consumption and quality of homogenization of milk after treatment in a stream homogenizer. To achieve this goal, a designed experimental setup was used. The dispersive indices of the milk emulsion were determined by computer analysis of micrographs of milk samples obtained with an optical microscope and a digital camera using Microsoft Office Excel and Microsoft Visual Studio C # software using the OpenCV Sharp library. As a result of experimental studies, the critical value of the Weber criterion for homogenization of milk was determined, which is 28. The regularities of dispersion of milk fat in a stream homogenizer with separate feeding of the fat phase have been established. It is determined that the milk treatment in the experimental homogenizer allows us to achieve an emulsion with an average size of fat globules of about 0.8 μm (at the level of valve homogenizers). The value of the homogenization coefficient is obtained for the disruption of the fat globule in the conditions: subject to a single effect on the emulsion, without the influence of vibration and cavitation. This homogenization coefficient equals 3300 m3/2.s-1.